Educational strategies and nursing theory to prepare leaners for NCLEX‐RN - Khalid Bandar Almasloukh; Melissa Miner; Kathleen Phillips; Michael Evans (Wiley, 2023)
Abstract Aim To identify teaching stategies, theories, and methods to enhance students' quality of life (QOL) that are used in preparing students for the NCLEX‐RN exam. Design A scoping review was conducted. Methods Arksey and O'Malley's methodological framework and PRISMA‐ScR guidelines were utilized. Data were derived from four databases including CINAHL, ERIC, PsychINFO and Web of Science using specific keywords. Inclusion criteria were English language and articles published in the last 7 years. Results Studies (N = 25) revealed that multiple educational strategies are used to prepare students for the NCLEX‐RN exam; however, there was not a consensus on a best practice. Eight theories were utilized in more than one article. QOL concerns of psychological, social, spiritual, financial and occupational dimensions may relate to the NCLEX‐RN results. Public Contribution Patterns in educational strategies and theories were noted among articles, but there was no focus on enhancing students' QOL.